2017
DOI: 10.1002/hep4.1082
|View full text |Cite
|
Sign up to set email alerts
|

Severe neonatal hyperbilirubinemia in Crigler‐Najjar syndrome model mice can be reversed with zinc protoporphyrin

Abstract: Neurotoxic bilirubin is solely conjugated by UDP-glucuronosyltransferase (UGT) 1A1. Due to an inadequate function of UGT1A1, human neonates develop mild to severe physiological hyperbilirubinemia. Accumulation of bilirubin in the brain leads to the onset of irreversible brain damage called kernicterus. Breastfeeding is one of the most significant factors that increase the risk of developing kernicterus in infants. Why does the most natural way of feeding increase the risk of brain damage or even death? This qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…This insufficiency in the pharmacokinetic study with Ugt1 -null mice is largely attributed to the early lethality of Ugt1 -null mice [33]. Most recently, it was revealed that Ugt1 -null mice that were treated with zinc protoporphyrin, which is a heme oxygenase-I inhibitor, avoided their extremely early lethality and they all became adults [102]. This methodology will allow the creation of complete Ugt knockout mice and completely humanized UGT mice.…”
Section: Discussionmentioning
confidence: 99%
“…This insufficiency in the pharmacokinetic study with Ugt1 -null mice is largely attributed to the early lethality of Ugt1 -null mice [33]. Most recently, it was revealed that Ugt1 -null mice that were treated with zinc protoporphyrin, which is a heme oxygenase-I inhibitor, avoided their extremely early lethality and they all became adults [102]. This methodology will allow the creation of complete Ugt knockout mice and completely humanized UGT mice.…”
Section: Discussionmentioning
confidence: 99%
“…). In cases of Crigler‐Najjar syndrome or Gunn rats where UGT1A1 is deficient, CYP1s play a role in the compensatory pathway of bilirubin metabolism …”
Section: Production Metabolism and Transport Of Bilirubinmentioning
confidence: 99%
“…This biliverdin–bilirubin redox cycle has been proposed to amplify antioxidant potency dramatically, although its significance has also been questioned . Elevation of serum bilirubin levels exerts a great impact on gene expression, which may be associated with the beneficial effects of bilirubin.…”
Section: Potential Benefits Of Hyperbilirubinemiamentioning
confidence: 99%
“…A BL é uma substância apolar e lipolítica encontrada no plasma na forma não conjugada (indireta), sendo transportada pela albumina para o fígado até ser captada pelos hepatócitos e convertida em bilirrubina conjugada (direta), a qual é tóxica em níveis elevados (5) . Pigmento de coloração amarelada, produzido principalmente pelas hemeproteínas encontradas nas hemácias, a BL é um importante marcador bioquímico utilizado no diagnóstico e monitoramento de doenças hepáticas e hematológicas (6) .…”
Section: Introductionunclassified
“…Embora quase sempre benigna, a hiperbilirrubinemia em neonatos requer avaliação cuidadosa e monitoramento, visando identificar os RN que podem desenvolver encefalopatia bilirrubínica ou kernicterus, doenças que podem ocasionar a morte do RN (10)(11) . A encefalopatia bilirrubínica (ECB) é uma patologia relacionada às manifestações clínicas agudas da toxicidade da BL nas primeiras semanas de vida, enquanto kernicterus se refere às sequelas permanentes com comprometimento representado por deficiências tênues do neurodesenvolvimento (3)(4)(5)(6)(7)(8) .…”
Section: Introductionunclassified